Accuracy of nutritional diagnostics for phosphorus considering five standards by the method of diagnosing nutritional composition in sugarcane - Pereira da Silva, Gilmara [UNESP]; Prado, Renato de Mello [UNESP]; Wadt, Paulo Guilherme Salvador; Moda, Leandro Rossato [UNESP]; Caione, Gustavo (Taylor & Francis Inc, 2020)
The accuracy of nutritional diagnoses can enable the definition of the best set of standards by the method of nutritional composition diagnosis (CND) in sugarcane. In this sense, the purpose of this study was to perform the accuracy of the nutritional diagnosis for phosphorus and to determine the best set of CND standards in sugarcane. A database of 720 samples was created, using the productivity and foliar concentrations of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn, and Zn. The criteria used to establish the norms populations were average productivity; average productivity + 0.5 standard deviation; average productivity + 1.0 standard deviation; average productivity + 1.5 standard deviations; and average productivity + 2.0 standard deviations. Variables studied included mean nutritional balance index (NBIm); CND index and productivity; and the degree of agreement between the standards and accuracies of the nutritional diagnoses for phosphorus by the method of Beverly and Hallmark. The lowest productivity loss was registered with the use of standard P1 and the largest losses with the use of standard P5 when compared to the other standards. Accuracy analysis of the nutritional diagnosis of phosphorus identified poor performance for all sets of CND standards, but better performance was obtained from reference populations of greater productivity.
Keywords: CND; reference population; Saccharum spp; validation